AFFIXATION ANALYSIS OF SONG LYRICS IN 9 SANORA ALBUM: A MORPHOLOGICAL STUDY - Agus Darma Yoga Pratama (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
Language is formed from rules, patterns and rules of language that have been agreed upon by a social group. The branch of linguistics that studies the basic units of language such as grammatical units is morphology. Morphology fights as the formation of words in a language. Affixation has a war in word formation in Nias language. Affixations can be added at the beginning, end and middle of a word. This study aimed to reveal the affixation of the song lyrics in the album 9 Sanora written in Nias language. The research method used qualitative methods with a descriptive qualitative approach. The source of the data in this study was vocabulary in the form of song lyrics from Album 9 Sanora written in Nias language. The agih method is used to analyze data in determining which part of the language is used as an object. Data analysis used the technique of changing the form of paraphrasing. Based on the results of data analysis, this study showed that there were 58 words that have affixation consisting of: 1) 51 words that have prefixes, namely prefixes {e-}, {ni-} {ma-}, {si-}, {i -}, {fa-}, {mo-}, and {te-}. 2) 5 words that have suffixes, namely suffixes